2023
DOI: 10.1108/jfra-02-2023-0066
|View full text |Cite
|
Sign up to set email alerts
|

Firms’ characteristics, corporate governance, and the adoption of sustainability reporting: evidence from Gulf Cooperation Council countries

Abstract: Purpose The purpose of the study is to investigate the factors that influence the adoption of new sustainability reporting (SDG) and external assurance (EXTA) practices. This study also examines the relationship between sustainability reporting activity and corporate economic performance for a sample of 99 companies in Gulf Cooperation Council (GCC) countries that addressed SDGs in their sustainability reports published in 2019. Design/methodology/approach Using a two-stage analysis, this study examines how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 151 publications
0
1
0
Order By: Relevance
“…On the other hand, the paper “Firms’ characteristics, corporate governance, and the adoption of sustainability reporting: evidence from Gulf Cooperation Council countries” (Al-Qudah and Houcine, 2024) aims to investigate the factors that influence the adoption of new sustainability reporting (SDG) and external assurance (EXTA) practices. This study also examines the relationship between sustainability reporting activity and corporate economic performance for a sample of 99 companies in GCC countries.…”
Section: Outline Of Articles In the Special Issuementioning
confidence: 99%
“…On the other hand, the paper “Firms’ characteristics, corporate governance, and the adoption of sustainability reporting: evidence from Gulf Cooperation Council countries” (Al-Qudah and Houcine, 2024) aims to investigate the factors that influence the adoption of new sustainability reporting (SDG) and external assurance (EXTA) practices. This study also examines the relationship between sustainability reporting activity and corporate economic performance for a sample of 99 companies in GCC countries.…”
Section: Outline Of Articles In the Special Issuementioning
confidence: 99%
“…State ownership can be described as a firm with the government holding a high percentage of shares in a company (Tam & Tan, 2007). Past studies found that firms in Malaysia, Singapore, and the Gulf Cooperation Council countries whereby the government is a substantial shareholder disclosed significantly more voluntary or CSR or sustainability information in their annual reports (Al-Qudah & Houcine, 2024;Boshnak, 2021;Eng & Mak, 2003;Ghazali, 2007;Said et al, 2009).…”
Section: Shareholders' Monitoring In Malaysiamentioning
confidence: 99%

Shareholders’ Monitoring and Online Disclosures of Minutes of Shareholders’ Meeting

Mohd Shazwan Mohd Ariffin,
Wan Nordin Wan-Hussin,
Siti Seri Delima Abdul Malak
et al. 2024
AAMJ